Academia at the crossroads: education and training in pharmacogenomics. (July 2012) - Lesko, Lawrence J; Johnson, Julie A
Technology and clinical research has catalyzed the growth of pharmacogenomics and personalized medicine. However, adoption of genetic and genomic findings into clinical practice has occurred at a much slower pace. There are a variety of reasons for this but almost everyone has identified education and training of healthcare providers, especially physicians, as an important enabler of personalized medicine. Numerous surveys have found that there is a knowledge gap in that most healthcare providers feel that genomics is an important determinant of disease and drug response but many feel inadequately informed to apply this information. This article explores this issue and proposes a way forward, recognizing that there will not be a one-size-fits-all approach to education and training for physicians and/or other healthcare providers.